COMP-11. CHROMATIN RUN-ON AND SEQUENCING (ChRO-seq) PROVIDES RETROSPECTIVE MOLECULAR PROFILING AND TRANSCRIPTIONAL ACTIVITY OF BRAIN TUMOR SPECIMENS UNSUITABLE FOR CONVENTIONAL RNA SEQUENCING. (5th November 2018) - Chu, Tinyi; Rice, Edward; Salamanca, Hans; Wang, Zhong; Longo, Sharon; Sweeney, Jared; Verhave, Brendon; Bodman, Alexa; Corona, Robert; Viapiano, Mariano; Chin, Lawrence; Danko, Charles
Abstract: The human genome encodes a variety of poorly understood RNA species that play important roles in the etiology complex disease yet remain challenging to identify in clinical isolates. We recently developed chromatin run-on and sequencing (ChRO-seq), a novel technology that maps the location of RNA polymerase genome-wide using virtually any frozen tissue sample, including samples with degraded RNA that are intractable to conventional RNA-seq. Here we report an integrative analysis of ChRO-seq maps from 61 primary human glioblastoma (GBM) tumors with matching clinical data, obtained from a retrospective cohort of patients banked at SUNY Upstate Medical Center (Syracuse, NY) between 1987 and 2007 (characteristics: Male:Female ratio= 2:1; median age at diagnosis= 59 years; median KPS=80; median overall survival= 343 days). Using ChRO-seq we discovered the boundaries and expression levels of annotated and unknown genes, lincRNAs, and active distal enhancers. Surprisingly, active enhancers in primary GBMs closely resembled the patterns found in the normal human brain, suggesting that malignant GBM tissue remains similar to the cell of origin. Despite extensive overall similarity, approximately 12% of enhancers were unique to GBMs. These enhancers drive regulatory programs similar to those in the developing nervous system and are enriched for transcription factor binding sites that specify a stem-like cell fate. More importantly, we discovered a core group of immune-related transcription factors and their associated binding sites whose activity is highly predictive of clinical outcomes in primary GBMs (HR= 2.66; p = 3.8e-4). Finally, we used the characteristic signatures of cell-type-specific enhancer activation to deconvolve the proportion of immune cell types infiltrating each tumor. Our study uncovers new insights into the molecular etiology of GBM and introduces ChRO-seq as a useful approach to map regulatory programs contributing to complex and heterogeneous diseases.